2011
DOI: 10.1097/qai.0b013e3181ff9750
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors of Recently HIV-Infected Men Who Have Sex With Men in the Year Postdiagnosis: Effects of Drug Use and Partner Types

Abstract: Objectives Assess behaviors of recently HIV-infected men who have sex with men (MSM). Methods From 2002–2006 193 recently HIV-infected MSM in the Southern California Acute Infection and Early Disease Research Program were interviewed every 3 months. Changes in HIV status of partners, recent unprotected anal intercourse (UAI), drug use, use of antiretroviral therapy (ART), detectable viral load and partnership dynamics over one year were used to predict recent UAI in a random effect logistic regression. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 40 publications
2
76
0
1
Order By: Relevance
“…In addition to being infectious, the undiagnosed population is also more likely to have unprotected sex compared with their diagnosed counterparts [27] and to contain those MSM who are experiencing primary infection (characterized by elevated viraemia [28]). In the UK, while the coverage of HIV testing is 82% among MSM attending sexual health clinics [11], only 55% of HIV-negative MSM reported an HIV test in the last year [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to being infectious, the undiagnosed population is also more likely to have unprotected sex compared with their diagnosed counterparts [27] and to contain those MSM who are experiencing primary infection (characterized by elevated viraemia [28]). In the UK, while the coverage of HIV testing is 82% among MSM attending sexual health clinics [11], only 55% of HIV-negative MSM reported an HIV test in the last year [29].…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, only 5% of the infectious population met treatment guidelines but were not receiving ART and most of these men went on to start treatment within the next 6 months. While more substantial gains could be achieved through expanding ART to MSM with CD4 counts < 500 cells/mL, an even greater impact could be achieved by halving the undiagnosed population and extending ART to all MSM with a CD4 count < 500 cells/mL.In addition to being infectious, the undiagnosed population is also more likely to have unprotected sex compared with their diagnosed counterparts [27] and to contain those MSM who are experiencing primary infection (characterized by elevated viraemia [28]). In the UK, while the coverage of HIV testing is 82% among MSM attending sexual health clinics [11], only 55% of HIV-negative MSM reported an HIV test in the last year [29].…”
mentioning
confidence: 99%
“…Studies of medication-assisted therapy to reduce methamphetamine use have, to date, mostly been negative, apart from one study of mirtazapine. 23 The proportionately greater methamphetamine use among referred participants, who were identified primarily through the STD Clinic and STD partner services, likely reflects the higher HIV/STD transmission risk among methamphetamine-using MSM 24,25 and further highlights the public health challenge of addressing methamphetamine as a barrier to HIV care and treatment and as a facilitator of HIV transmission. Many substance users did not identify their substance use as an important barrier to care.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, one-third of HIV-positive MSM reported methamphetamine use and unprotected anal intercourse, a pattern that remained consistent over time [24]. In a sample of racially diverse HIV-positive MSM in medical care in San Francisco, methamphetamine users reported an increased rate of unprotected sex among [19•].…”
Section: Methamphetamine Use and Unprotected Sexmentioning
confidence: 99%